(untitled) (Environment & Health, 2025)
Purpose – to determine the features of the content of essential microelements - Co, Cr, Cu, Zn in the blood serum of residents of the industrial region under environmental influence and its changes during urological pathology. Materials and methods - to assess the microelement status, the content of cobalt, chromium, copper and zinc in the blood serum of a clinically healthy adult population and urological patients - residents of an industrial region was studied by the method of atomic emission spectrometry on an atomic emission spectrometer with inductively coupled plasma iSAP 7200 Duo, No. IC72DC164705, USA, Thermo Fisher Scientific. Results. The peculiarities of the content of a number of essential microelements in the blood serum of clinically healthy residents of the industrial region compared to the results of studies conducted in the zone of ecological and hygienic optimum, with a reliably 1,2-1,3 times higher, according to average values, the content of chromium, the correspondence of the concentration of cobalt and zinc and the lower concentration of copper. The development of urological pathology is accompanied by the formation of a trace element imbalance, which is manifested by a significant increase in the concentration of copper by 1.4 times with a slight increase in the content of cobalt and chromium, a decrease in the concentration of zinc. We found correlation in 42% of correlation matrices with the presence of both a direct correlation between the content of Co and Zn, Co and Cr, Cr and Zn, which increased in urological pathology, and a negative one in the binary system Co-Cu in the control group in the absence of a significant dependence in patients with pyelonephritis. The coefficients of the ratio Co/Cu and Cr/Cu decreased by 20% in the group of urological patients compared to the control group, Co/Zn increased by 33%, Cr/Zn by 22%, Cu/Zn by 51%, which indicates the development of microelement imbalance in blood serum in urological pathology. Conclusions. The identified features of microelement status are an important informative base for improving biomonitoring, timely prediction of probable deterioration of health due to environmental impact and the development of urological pathology, development of a complex of public health measures, optimization of medical and diagnostic approaches to improve the health of the population.